Using Experts` Opinions Through Delphi Technique - Yousuf, Muhammad Imran (Practical assessment, research & evaluation, 2007)
The Delphi technique provides different opportunities to researchers than survey research. Essential components of the Delphi technique include the communication process, a group of experts, and essential feedback. This paper provides the foundations of the Delphi Technique, discusses its strengths and weaknesses, explains the use and stages followed, discusses panel selection, and explains how consensus among participants is reached.